Reliability of estimated glomerular filtration rate in patients treated with platinum containing therapy. Issue 7 (7th March 2014) - Lauritsen, Jakob; Gundgaard, Maria G.; Mortensen, Mette S.; Oturai, Peter S.; Feldt‐Rasmussen, Bo; Daugaard, Gedske
Abstract : Estimates of glomerular filtration rate (eGFR) are widely used when administering nephrotoxic chemotherapy. No studies performed in oncology patients have shown whether eGFR can safely substitute a measured GFR (mGFR) based on a marker method. We aimed to assess the validity of four major formulas based on PCr (Cockcroft‐Gault, MDRD, Wright and CKD‐EPI) in comparison to mGFR in an oncology setting. Patients included had disseminated germ cell cancer and received conventional chemotherapy: bleomycin, etoposide and cisplatin. The mGFR of the patients was compared to all estimates with focus on bias (median percentage error), precision (median absolute percentage error) and accuracy (p10 and p30). The precision of carboplatin dosage based on eGFR was calculated. Data on mGFR, eGFR, and PCr were available in 390 patients, with a total of ∼1, 600 measurements. Median PCr and mGFR synchronically decreased after chemotherapy, yielding high bias and low precision of most estimates. Post‐chemotherapy, bias ranged from −0.2% (MDRD after four cycles) to 33.8% (CKD‐EPI after five cycles+), precision ranged from 11.6% (MDRD after four cycles) to 33.8% (CKD‐EPI after five cycles+) and accuracy (p30) ranged from 37.5% (CKD‐EPI after five cycles+) to 86.9% (MDRD after four cycles). Although MDRD appeared acceptable after chemotherapy because of high accuracy, this equation underestimated GFR in all other measurements. Before and years after treatment, Cockcroft‐Gault and Wright offered best results. Precision of carboplatin dosage was low. In conclusion, bias, precision and accuracy were unacceptable in all equations due to a synchronous decrease of PCr and mGFR during chemotherapy. Abstract : What's new? Estimates of renal function based on plasma creatinine levels are notoriously unreliable during and after chemotherapy, but are frequently used to substitute for true measurements of the glomerular filtration rate (GFR). The authors compared different formulas of estimated versus measured GFR in patients with germ cell cancer receiving conventional chemotherapy. They find that estimates of GFR are highly unreliable when drugs with a nephrotoxic potential are included in the chemotherapeutic regimen. This study supports a recommendation to precisely measure GFR with suitable radiotracers in these cases.